Customary land disputes and the commoditisation of rural land in Africa: a case study from eastern Uganda. Issue 3 (3rd July 2022) - Kandel, Matt
ABSTRACT: This paper considers a customary land dispute within the context of rising land commoditisation in the Teso region of eastern Uganda. I analyse a statutory court-led mediation hearing of the land dispute, which I observed in October of 2015 in Teso. My analysis of the hearing focuses on how key aspects of the dispute should be understood within the broader context of customary land commoditisation and agrarian change in Teso, exemplifying what Chimhowu calls the '"new" customary tenure' in Africa. In support of an historical approach to understanding land tenure change, I underline the spatial and temporal dynamics of land commoditisation in the region. While the commoditisation of customary land is a trend widely observed across rural Africa, it is less clear how land dispute resolution policies will adapt to this structural shift in customary land tenure.